Insights into the nuclear export of murine leukemia virus intron-containing RNA - Pessel-Vivares, Lucie (RNA Biol, 2015)
The retroviral genome consists of an intron-containing transcript that has essential cytoplasmic functions in the infected cell. This viral transcript can escape splicing, circumvent the nuclear checkpoint mechanisms and be transported to the cytoplasm by hijacking the host machinery. Once in the cytoplasm, viral unspliced RNA acts as mRNA to be translated and as genomic RNA to be packaged into nascent viruses. The murine leukemia virus (MLV) is among the first retroviruses discovered and is classified as simple Retroviridae due to its minimal encoding capacity. The oncogenic and transduction abilities of MLV are extensively studied, whereas surprisingly the crucial step of its nuclear export has remained unsolved until 2014. Recent work has revealed the recruitment by MLV of the cellular NXF1/Tap-dependent pathway for export. Unconventionally, MLV uses of Tap to export both spliced and unspliced viral RNAs. Unlike other retroviruses, MLV does not harbor a unique RNA signal for export. Indeed, multiple sequences throughout the MLV genome appear to promote export of the unspliced MLV RNA. We review here the current understanding of the export mechanism and highlight the determinants that influence MLV export. As the molecular mechanism of MLV export is elucidated, we will gain insight into the contribution of the export pathway to the cytoplasmic fate of the viral RNA.